Distributed Cognition and Aesthetics of Fragmentary Accumulation in Vivian Abenshushan's "Permanente obra negra" - Mora, Vicente Luis (Tropelías: Review of Literary Theory and Comparative Literature, 2022)
One of the particularities of contemporary narrative fragment lays in its self-consciousness and its reflective proclivity about its unfinished condition. This recurrent peculiarity will be analyzed from the novel Permanente obra negra, of Mexican author Vivian Abenshushan, which mixes research about fragmentarism and use of textual and technic mechanisms of distributed cognition, mechanisms that will be examined from a neurocognitive approach. Abenshushan’s novel (or narrative piece) constitutes an example of questioning all the dimensions of the literary experience and, in some way, a work that proposes a non-unitary narrative poetics to 21th century.
Keywords: Distributed cognition; narrative; literary fragment; fragmentarism